Utilization of Scientific Publication Media to Improve the Quality of Scientific Work - Aini, Qurotul; Handayani, Indri; Lestari, Fauziyyah Husna Nurdiayanah (APTISI Transactions on Management (ATM), 2020)
The publication of scientific work is an absolute thing that must be owned and produced by academics at this time. Moreover, when referring to the Minister of Administrative and Bureaucratic Reform (PAN RB) Regulation No. 17 of 2013 and the Minister of Education and Culture Regulation No. 92 of 2004 which states that the increase in the academic level of lecturers requires publication of accredited national scientific journals and journals internationally reputable in their field. In addition to being very important for the performance of lecturers, the publication of scientific papers has become a government regulation through the Director General of Higher Education, which requires S1, S2 and S3 students to make a summary of scientific work published both online and in print as one of the graduation requirements. Seeing this, Raharja College has participated in providing publication media for scientific works, especially in online forms, one of which is iLearning Journal Center (iJC). Until now iLearning Journal Center has overseen 5 (five) journals in it with different scope of research. However, the problems that occur at this time are still a lack of the general public to know especially in the Higher Education environment regarding the iLearning Journal Center (iJC) as a publication media for online scientific work. In this study will be discussed about the steps or methods taken to maximize the use of iLearning Journal Center (iJC) as an online journal publication media to improve the quality and quantity ofscientific works. This study uses SWOT analysis method and system design using the Unified Modeling Language (UML) and the applications used in this study by applying the Open Journal System (OJS) which is known as management software and publishing online journals. The results of this study are a governance or management that can be done as a step to maximize the increase of publication of online scientific works for the academic community.